Strategi Komunikasi dalam Pengembangan Wisata Edukasi Laut Bagi Wisatawan Remaja di Pulau Malahing Kota Bontang - Nurfadilah Nurfadilah; Moh. Mustakim; Auliansyah Auliansyah; Paulus Taru; minullah Amirul Amin (Universitas Teuku Umar, 2023)
Traveling is an activity that can entertain and calm the heart and mind, so tourism activities are needed. Indonesia is very well known as a tourist spot, one of which is a tourist location that is a mainstay of tourism in the City of Bontang, namely Malahing Island. Malahing Island is one of the tourist sites in East Kalimantan and has many tourist objects. However, the management of tour packages is still based on entertainment for tourists. Therefore this service is carried out as a form of socialization of marine tourism education on Malahing Island so that tourists can add insight into the sea through tourism education. The activities include outreach to young tourists regarding maritime biota tourism education and introducing tourist attractions on Malahing Island. The outreach results regarding educational tourism found that in the category of understanding, as much as 77% of teenage tourists understood the content of socialization, and 23% in the type very well understood the socialization results. In contrast, the educational tourism interest survey results found that 69% were interested in traveling using the educational method, and as many as 31% of tourists were very interested. Young tourists are interested in traveling because educational tours can add insight to tourists indirectly. After all, the entertainment provided can be valuable as insightful information about marine tourism education.